SİSPLATİN İLE OLUŞTURULAN NEFROTOKSİSİTEDE EPİGALLOKATEŞİN-3- GALLAT'IN MAPK, IL-6 VE TNF-ALFA PROTEİN SİNYAL YOLAKLARINA ETKİSİ - TOPRAKOĞLU, NURAN (Fırat Üniveristesi, 2021)
Kanser hastalarının tedavisinde kemoterapi ilacı olarak kullanılan sisplatin, kalıcı böbrek yetmezliğine yol açacak şekilde ciddi bir nefrotoksisite oluşturmaktadır. Bu çalışmada, sıçanlara sisplatin tek doz ve intraperitoneal olarak uygulanmıştır. Sisplatinin yol açacağı nefrotoksisiteye karşı antioksidan ve antiinflamatuar özelliklere sahip polifenolik bir kateşin olan EGCG tedavisinin nefrotoksisite ve dokuda oluşan hasara karşı koruyucu etkilerinin belirlenmesi amaçlanmıştır. Böbrek dokusunda ve plazmada EGCG'nin uygulandığı gruplarda, malondialdehit (MDA) seviyesinin azaldığı, katalaz (CAT) aktivitesinin ve glutatyon (GSH) seviyesinin ise arttığı gözlenmiştir. EGCG ile tedavi edilen grupta (Cis+EGCG) inflamasyon belirteci olan p38? MAPK, IL-6 ve TNF-? protein ekspresyon seviyelerinin, sisplatin (Cis) grubuna kıyasla önemli bir şekilde azaldığı belirlenmiştir (p<0,05). Histopatolojik incelemede sisplatin uygulaması yapılan grupta belirgin olarak böbrek hasarının oluştuğu, buna karşın EGCG verilen grupta ise azaldığı görülmüştür. Bu sonuçlar, sisplatin ile oluşturulan nefrotoksisitede, EGCG ile yapılan tedavinin antiinflamatuar etki gösterdiği ve nefrotoksisiteyi önemli ölçüde önleyebileceğini göstermektedir

Cisplatin, which is used as a chemotherapy drug in the treatment of cancer patients, creates a serious nephrotoxicity that leads to permanent kidney failure. In this study, cisplatin was administered to rats as a single dose and intraperitoneally. It was aimed to determine the protective effects of EGCG treatment, which is a polyphenolic catechin with antioxidant and anti-inflammatory properties, against nephrotoxicity caused by cisplatin, against nephrotoxicity and tissue damage. It was observed that malondialdehyde (MDA) level decreased, catalase (CAT) activity and glutathione (GSH) level increased in groups where EGCG was applied in kidney tissue and plasma. It was determined that the expression levels of p38? MAPK, IL-6 and TNF-? proteins, which are inflammation markers, were significantly decreased in the EGCG-treated group (Cis+EGCG) compared to the cisplatin (Cis) group (p<0.05). In the histopathological examination, it was observed that kidney damage occurred significantly in the cisplatin-administered group, whereas it decreased in the EGCG-administered group. These results show that in cisplatin-induced nephrotoxicity, treatment with EGCG has an anti-inflammatory effect and can significantly prevent nephrotoxicity.
The effect of epigallocatechin-3-gallat on MAPK, IL-6 and TNF-alpha protein signaling pathways in cisplatin-induced nephrotoxicity
Keywords: Biyoloji